Digitalisation of University Education and Research as Consequence of the Covid-19 Pandemic – A Paradigmatical Change - Koos, Stefan (Universitas Muhammadiyah Surabaya, 2022)
The compulsion to work from home and contact restrictions has given digitalisation a greater push than it ever had before. As is often the case when a development process is not slow but forced and accelerated by external influences, dislocation occurs because people are rather slow to adapt to new circumstances. We see a quick change in teaching methods, a digitalization of teaching, but at the same time we see tendencies to continue behaviours of face-to-face teaching and not to adapt to the new processes. This applies equally to both students and lecturers. The article is based on a presentation of the author at the ‘1st Multidisciplinary International Conference on Potential of Research during Pandemic’ on 15.-16. Dezember 2021 at the Universitas Muhammadiyah Surabaya. It aims to give an exemplary insight of legal and didactic issues in university law teaching in Germany. Most of these issues may be transferrable to the teaching situation in Indonesia. The paper concludes that the accelerated digitalization of university teaching, which may be more than just an intermediary substitute to traditional teaching methods, needs behavioural changes of lecturers and of students. Furthermore, it pleads for a more pragmatical approach in data protection law.Keywords: digitalisation; teaching methods; data protection; examination law.